Headaches and exercise - McCrory, P. (Sports Medicine, 2000)
Exercise-related headache is one of the most common medical problems affecting the modern-day athlete. Despite the high prevalence of headache in community populations, the epidemiology of sports-related headache is unclear. In certain collision sports, up to 50% of athletes report regular headaches as a consequence of their athletic participation. The classification of the different types of sport-related headache by the International Headache Society (IHS) and in previously published articles does not adequately encompass the clinical problem faced by team physicians. Confusion exists where terms such as 'effort headache' and 'exertional headache' may be used to describe similar entities. In this review, the specific headache entities discussed include benign exertional headache, effort headache, acute post-traumatic headache and cervicogenic headache. For the sports physician, an understanding of the variety of specific headache syndromes that occur with particular sports is necessary for everyday clinical practice. This article reviews the common exercise-related headache syndromes and attempts to provide a framework for their overall management. Team physicians also need to be cognisant that many of the standard preparations used to treat headaches may be banned drugs under International Olympic Committee (IOC) rules.